Effect of autoclaving cycles on the surface topography of endodontic nickel-Titanium rotary files: A systematic review - Nikhil B Nighot; Anamika C Borkar; Soumya S Shetty; Nitika Tiwari; Sayali A Maral; Shruti Kamath (Wolters Kluwer Medknow Publications, 2019)
The surface topography of nickel-titanium (Ni-Ti) rotary files, after being exposed to a specific number of sterilization cycles in an autoclave, can cause surface changes in the file. Hence, the use of AFM and scanning electron microscopy would help to shed some light on the delicate balance between the action of steam sterilization and its reaction, in terms of topographical changes on the surface of the instrument, which could have implications in its clinical use. To analyze the effect of autoclave cycles on the surface topography of endodontic Ni-Ti rotary files. English-language articles were retrieved from electronic biomedical journal databases. PubMed, Google Scholar, and ResearchGate were used to complete the search for all full-text articles available. The search was done till September 30, 2018. The last data search was conducted on September 30, 2018. All articles that were published in English were included. Only those articles that were published between January 1, 2000, and September 30, 2018, comparing the effect of autoclaving cycles on the surface roughness of Ni-Ti rotary files, were included. Autoclave cycles. A total of 62 articles were identified through electronic database searching. After duplicate removal, and full-text reading, six articles qualified for qualitative synthesis in this systematic review. Autoclave sterilization causes an increase in the surface roughness of Ni-Ti files; the increase in roughness corresponds to the number of autoclave cycles that the instruments were exposed to.